Mutual insurance in the entrepreneurial landscape - Irina L. Logvinova; Yury B. Rubin; Mikhail V. Lednev; Daniel P. Mozhzhukhin (Journal of Innovation and Entrepreneurship, 2022)
In this article, the authors introduce mutual insurance as a constructive component of the modern entrepreneurial landscape aimed at the protection of the wealth-related interests of the participants of the mutual insurance company (mutual insurance society, friendly society, etc.). Analyzing mutual insurance, the authors display it from the standpoint of entrepreneurship and assume that such companies (MICs) are among the insurance market actors. The specific feature of MICs is that they form the community of their members-policyholders. As far as members of each organization of this kind are its co-owners, they carry out some critical entrepreneurial activity functions. The object of this research is represented by the insurance market of the Russian Federation, through the prism of which the degree of development of MICs was demonstrated, and the barriers to its infrastructure growth were determined.
Keywords: 650; Entrepreneurship; Features and functions of entrepreneurship; Members of mutual insurance organization; Mutual insurance; Mutual insurance organization